Modelagem e simula??o de QoS em rede GPRS - Siqueira, Giovani Prado (2004)
It is envisaged in the near future that a number of real-time applications based on voice, video and data can be accessed from mobile stations supported by wireless technologies. However, there are still obstacles to such applications being provided with satisfactory quality of service. The present work proposes a simulation model that will aid in the analysis of the performance of a General Packet Radio Service (GPRS) network from the implementation of different QoS (Quality of Service) mechanisms. These mechanisms provide a differential treatment to the traffic of various types of media. The results obtained from simulations of the proposed model allow a comparative evaluation between the different mechanisms implemented (scheduling disciplines: FIFO, PQ, WFQ, WRR and DWRR